Prevention of typhoid by Vi conjugate vaccine and achievable improvements in household water, sanitation, and hygiene: evidence from a cluster-randomized trial in Dhaka, Bangladesh - Tadesse, BT; Khanam, F; Ahmmed, F; Im, J; Islam, MT; Kim, DR; Kang, SSY; Liu, X; Chowdhury, F; Ahmed, T; Binte Aziz, A; Hoque, M; et al. (Oxford University Press, 2022)
Background Typhoid fever contributes to approximately 135 000 deaths annually. Achievable improvements in household water, sanitation, and hygiene (WASH) combined with vaccination using typhoid conjugate vaccines (TCVs) may be an effective preventive strategy. However, little is known about how improved WASH and vaccination interact to lower the risk of typhoid.